PENGARUH BAHAN TAMBAH PLASTIMENT-VZ TERHADAP SIFAT BETON - Maricar, Shyama; Tatong, Burhan; Hasan, Hajatni (MEKTEK, 2013)
Concrete mixture for structure of the building is expected to according to the quality and specifications desired. With the addition of admixtures materials used for concrete mix, it is necessary to know the type, properties and benefits of admixture produced by various companies. Concrete used In this study were added admixtureof Plastiment-VZ for characters investigated.In this study used two variations of concrete, ie normal concrete and concrete with the addition PlastimentVZ with usage percentage of 0.20%, 0.40% and 0.60% of the weight of the cement used in normal concrete. Cylindrical specimens used for compressive strength testing with a total of 3 pieces for each test.The test results obtained average compressive strength of normal concrete (f'cr) of 27.554 MPa, and for concrete with the addition of-VZ Plastiment of 0.20% obtained an average compressive strength, f'cr = 29.252 MPa, the concrete with the addition of Plastiment-VZ 0.40%, obtained f'cr = 30.951 MPa, whereas the addition of 0.60% for the compressive strength at 28 days obtained at 32.083 MPa.Keywords: Compressive strength, Plastiment-VZ